IoMT Supported COVID Care – Technologies and Challenges - R. John Martin (International Journal of Engineering and Management Research, 2022)
The Internet of Things (IoT) has sparked substantial progress in the recent days of pandemic and achieved several milestones especially in healthcare. Wearable technologies have gained in popularity as a means of ensuring the health and safety of users in medical and disaster relief activities, facilitating the evolution of the Internet of Medical Things (IoMT). The IoMT is a phenomenon in which computer networks and medical equipment are linked over the Internet to allow physicians and patients to interact in real time. This coronavirus pandemic has demonstrated how unprepared our systems are for a disaster of this magnitude, as well as the necessity for robust, computationally intelligent, and profound meddling. This study piece looks at the many IoT-enabled smart solutions that could be used to respond to various aspects of this rising epidemic, from diagnosis to treatment to prevention. The paper provides a retrospective survey and identifies several obstacles and obstructions to IoT integration as an attempt to deal with coronavirus pandemic. The work concludes with a discussion of challenges and future scope to the difficulties mentioned in the bench marked works.